Student Grade Prediction by using Machine Learning Methods and Data Analytics Techniques - , Anoushka; Dubey, Shivani; Singhal, Vikas (International Journal of Scientific Research in Computer Science and Engineering, 2022)
In the world of an open education system, students have the flexibility to learn anything with ease as the learning content is easily available. This can make the student rather confident as well as careless at the same time. Therefore, it becomes challenging to predict the performance of the student beforehand. In this research, an attempt is made to improve the students’ situations by predicting their performance in advance. This is done by applying the univariate linear regression model. This would help the students improve their performance based on predicted grades and enable teachers to identify those who need assistance. The Main objective of this paper is to implement a simple algorithmic model that predicts the score an individual student that he/she will get at the end of the year. “G3” or the final grade is our label (output) and the rest of the columns will be our features (inputs).